Nanomaterials and plastic deformation : selected, peer reviewed papers from the Annual Meeting of Chinese Materials Research Society, Session L, 2009, 12-17 September 2009, Suzhou, China - Wang, Jing Tao (Trans Tech Pub., 2011)
The deformation-processing of advanced materials having ultrafine- or nano-structures, and therefore significantly improved properties, has developed into one of the most promising frontiers of materials science and technology. The present 35 peer-reviewed papers cover many aspects of Nanomaterials and Plastic Deformation and will provide a succinct introduction to the subject. Review from Book News Inc.: The session also served as the fourth symposium succeeding the serial symposia Ultrafine Grained and Nanostructured Materials, so those materials are particularly featured in the 35 selected.
Keywords: Deformations (Mechanics) -- Congresses.; Nanostructured materials -- Plastic properties -- Congresses.; Nanotechnology -- Congresses.; elektronické knihy; electronic books